The Impact of Using a Mixture of Organic Fertilizers (Compost And Liquid Organic) and Plastic Mulch, on the Development of Cayenne Pepper Plants - Albert Tulak; Inrianti Inrianti; Maulidiyah Maulidiyah; Muhammad Nurdin (Green Engineering Society, 2022)
Husoak Village, Hubikiak District Jayawijaya is one of the regions in Papua province where plants including chili. The cultivation system are extensively and using traditional method depending on soil nutrients. The aim of the research is to see how utilizing a mix of organic fertilizer and mulch affects the growth and development of chili plants. This research was conducted based on a randomized block design consisting of 4 treatments. namely P1 = compost; P2 = compost + liquid organic fertilizer + plastic mulch; P3 = compost +TiO2+liquid organic fertilizer + plastic mulch; P4= Control (No Treatment). When compared to the control. the results showed that using a mix of organic fertilizer (compost and liquid organic) and mulch had an effect that was not significant. This demonstrates that cayenne pepper plants may still get the nutrients they require from nutrients available in the soil. Fertile land is still classified as cultivated land.